PUBLIC POLICIES DEVELOPED IN WOMEN'S PRISONS IN ARGENTINA - Brito, Tiago Silva (Seven Editora, 2024)
The main objective of this paper is to analyze the public policies of rupture in women's prisons in Argentina, seeking to understand their implications for social reintegration, the reduction of recidivism and respect for the human rights of incarcerated women. The study addresses the programs developed in the prison context for women, analyzing the conditional guidelines of international bodies, as well as the Argentine legislation that aims to promote the dignity and rehabilitation of these inmates. Starting from a theoretical and methodological review, questions were raised about relative gender inequalities, the conditions of incarceration and the challenges of resocialization. The theoretical framework covers studies on gender, criminal policies and human rights, providing a critical and multidimensional view. A qualitative approach was used, with documentary analysis and interviews with professionals from the penitentiary system. The final considerations reveal that, although there has been progress in foreign policies for the female prison population, inequalities persist and deactivate greater attention from the State and civil society. It is concluded that the effectiveness of policies depends on an integrated approach, focusing on the empowerment of women and combating the conditions of social exclusion that many face before and after incarceration. DOI:https://doi.org/10.56238/sevened2024.037-023